2014
DOI: 10.1111/jgh.12448
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia induced by adenosine 5′‐monophosphate attenuates injury in an L‐arginine‐induced acute pancreatitis rat model

Abstract: Hypothermia induced by 5'-AMP could inhibit the acute inflammatory reaction and NF-κB activation associated with acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…Large exogenous doses of AMP (500 to 3500 mg/kg) cause torpor and have protective effects in various injury models (Miao et al , 2015; Miao et al , 2012; Tao et al , 2011; Wang et al , 2014). There is no clearly identified receptor for AMP (although AMP has been proposed to be an A 1 AR ligand (Rittiner et al , 2012)).…”
Section: Discussionmentioning
confidence: 99%
“…Large exogenous doses of AMP (500 to 3500 mg/kg) cause torpor and have protective effects in various injury models (Miao et al , 2015; Miao et al , 2012; Tao et al , 2011; Wang et al , 2014). There is no clearly identified receptor for AMP (although AMP has been proposed to be an A 1 AR ligand (Rittiner et al , 2012)).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that Wistar rats given 5′-AMP at a dose of 0.5 g/kg body weight enter a state of torpor approximately 90 min after the injection at an AT of 16°C, and that AIH could downregulate inflammation [14]. In this study, we found that AIH could decrease the levels of CD14, CRP and TLR4 in endotoxemic rats and inhibit the activation of the ERK1/2, p38, NF-κB and JNK pathways.…”
Section: Discussionmentioning
confidence: 61%
“…When administered at a sufficient dose, 5′-AMP allows nonhibernating mammals to rapidly undergo reversible and safe severely hypothermic reactions at ambient temperatures (ATs) of 15-16°C [9][10][11][12][13]. Recently, studies have shown that hypothermia induced by 5′-AMP has an anti-inflammatory effect [10,11,14]. Our previous studies have also shown that hypothermia induced by 5′-AMP could inhibit LPS-induced inflammation [15].…”
Section: Introductionmentioning
confidence: 95%
“…Tan et al [35] showed that higher activity of MMP-9 coexists with higher concentrations of UA and higher IMT. In opposition to the abovementioned results in an experimental animal study performed in rats showed that UA-induced inflammation led to a decrease in MMP-9 activity [36]. Similarly, UA administration during acute phase of ischemic stroke decreased the activity of proinflammatory MMP-9 [37].…”
Section: Discussionmentioning
confidence: 72%